Circular economy indicators for measuring social innovation in the Brazilian textile and fashion industry. (20th August 2022) - Galatti, Leticia Gabriela; Baruque-Ramos, Julia
Abstract: The Brazilian textile and fashion industry impacts directly and indirectly 8 million people, a context in which social indicators become even more significant. However, while job creation has been highlighted as one of the social benefits of the circular economy, few social indicators have been explicitly included for its impact measurement. Furthermore, considering that tools and methods are needed to link business decisions with social effects, social sustainability measures are needed. Based on the literature review, this research has identified indicators to measure the capacity of the Brazilian textile and fashion industry to promote social innovation in the circular economy. The 37 indicators identified were rated on a 7-point Likert scale by 29 experts representing the industry, representative entities of the textile and fashion sector, and institutions engaged in human and labour rights. Three other indicators were appointed by the experts. As result, 40 indicators are proposed according to the classification: employment; labour/management relations; occupational health and safety; training and education; diversity and equal opportunity; and fair distribution of income. These findings can provide a practical tool for circular economy practitioners and researchers and contribute to the improvement of measuring methods and monitoring of the social aspects of labour towards the circular economy in the textile and fashion industry. Graphical abstract: Image 1 Highlights: Social innovation plays an important role in improving social justice. Social innovation can be driven through the circular economy. Brazilian textile and fashion sector has potential to promote social innovation. Forty indicators of social innovation in the Brazilian context were proposed. The indicators offer a practical tool for fashion practitioners and academics.